Current European data collection on emergency department presentations with acute recreational drug toxicity: Gaps and national variations. (December 2014) - Heyerdahl, Fridtjof; Hovda, Knut Erik; Giraudon, Isabelle; Yates, Christopher; Dines, Alison M.; Sedefov, Roumen; Wood, David M.; Dargan, Paul I.
Abstract Background. The number of new (novel) psychoactive substances (NPS) available in the illegal market is increasing; however, current monitoring of the drug situation in Europe focuses mainly on classical drugs of abuse, with limited emphasis on clinical presentation in the emergency department (ED). The European Drug Emergencies Network (Euro-DEN) is a European Commission-funded project that aims to improve the knowledge of acute drug toxicity of both classical recreational drugs and NPS. As a baseline for this project, we performed a study to establish which data are currently being collected and reported in Europe on ED presentations with acute toxicity related to NPS and classical drugs of abuse. Methods. We used a three-pronged approach to identify any systematic collection of data on NPS toxicity in Europe by i) performing a literature search, ii) utilising an online survey of the European Monitoring Centre for Drugs and Drug Addiction Re seau Europe en d'Information sur les Drogues et les Toxicomanies national focal points and iii) exploiting the knowledge and resources of the Euro-DEN network members. Results. The literature search revealed 21 papers appropriate for assessment, but only one described a systematic collection of clinical data on NPS. Twenty-seven of thirty countries responded to the online survey. More than half of all the countries (52%) did not perform any registration at all of such data, 37% collected systematic clinical data on NPS at a national level, while 44% collected data on classical drugs. A few examples for good practice of systematic collection of clinical data on ED presentations due to acute toxicity were identified. Conclusion. The systematic collection of data on ED presentation of toxicity related to NPS and classical drugs in Europe is scarce; the existing collection is limited to single centres, single countries, groups of patients or not focused on novel drugs; the collection of data is highly variable between the different countries. Euro-DEN, a European Commission funded project, aims at closing some of these gaps.